2021
DOI: 10.1371/journal.pone.0252997
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trinidad community stakeholder perspectives on the use of yeast interfering RNA-baited ovitraps for biorational control of Aedes mosquitoes

Abstract: Dengue, Zika, chikungunya and yellow fever viruses continue to be a major public health burden. Aedes mosquitoes, the primary vectors responsible for transmitting these viral pathogens, continue to flourish due to local challenges in vector control management. Yeast interfering RNA-baited larval lethal ovitraps are being developed as a novel biorational control tool for Aedes mosquitoes. This intervention circumvents increasing issues with insecticide resistance and poses no known threat to non-target organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Given the constant search for better sustainable measures for the control of arbovirus vectors 7 - 29 , the present study provides important information on the use of SAP in ovitraps. The addition of hydrated SAP to the traditional ovitrap proved operationally efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the constant search for better sustainable measures for the control of arbovirus vectors 7 - 29 , the present study provides important information on the use of SAP in ovitraps. The addition of hydrated SAP to the traditional ovitrap proved operationally efficient.…”
Section: Discussionmentioning
confidence: 99%
“…It is customary to add oviposition attractants to enhance productivity 16 , 21 . Other resources have been added to ovitraps, such as insecticides, microbial larvicides, pheromones, entomopathogenic fungi, and yeast ribonucleic acid (RNA) interference, to hinder the development of immature stages of vector mosquitoes 10 , 22 - 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the need to consider property inaccessibility in planning for future studies and how best to develop strategies that at a minimum would include efforts directed at more dense trap placements around the perimeters of these properties. We did simultaneously conduct several community engagement activities across Trinidad, including the Curepe area, prior to this study 52 , 53 , wherein we found that most residents were knowledgeable about mosquito biology and disease transmission, and also supportive of our yeast interfering RNA larvicides and their use in lethal ovitraps. Thus, it seems likely that including expanded community engagement activities prior to, and during future ovitrap trials, could promote increased neighbor-to-neighbor interactions that would facilitate access to and placement of ovitraps more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these insecticides to kill both larvae and adults opens opportunities to design integrated RNAi mosquito control programs in which a combination of methods, such as larvicidal treatment of breeding sites with interfering RNA larvicides, larval lethal lure-and-kill interfering RNA ovitraps [17], and RNAi-ATSBs is used simultaneously. Recent studies have uncovered a high level of acceptance of yeast RNAi-based larvicides and ovitraps among stakeholders in Trinidad and Tobago [59,60]. An engagement study in Tanzania [61] evaluated stakeholder acceptance of ivermectin-based ATSBs.…”
Section: These High Feeding Rates (Tablementioning
confidence: 99%